2003
DOI: 10.1002/jae.711
|View full text |Cite
|
Sign up to set email alerts
|

Testing long‐run PPP with infinite‐variance returns

Abstract: SUMMARYThis paper investigates the long-run purchasing power parity hypothesis when exchange rate returns and inflation rates are assumed to be heavy-tailed stochastic processes. More specifically, residual-based and likelihood-ratio-based cointegration tests of PPP that explicitly allow for infinite-variance innovations are applied to monthly data (1973 : 1-1999 : 12)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
1
22
1
8
Order By: Relevance
“…When we apply the partially adaptive test to these series, we rejected the unit root hypothesis in real GNP, supporting the literature of transitory uctuations about trend. We were unable to reject the null of unit root in real exchange rates, implying that, as reported in Falk and Wang (2003), the purchasing power parity hypothesis may not hold in the long run even if tail heaviness are accounted for. We also found no evidence against unit root in nominal interest rate, which supports the ndings in Rose (1988) and raises doubt about economic results predicted by the CCAPM and optimal monetary policy models.…”
Section: Introductioncontrasting
confidence: 53%
See 2 more Smart Citations
“…When we apply the partially adaptive test to these series, we rejected the unit root hypothesis in real GNP, supporting the literature of transitory uctuations about trend. We were unable to reject the null of unit root in real exchange rates, implying that, as reported in Falk and Wang (2003), the purchasing power parity hypothesis may not hold in the long run even if tail heaviness are accounted for. We also found no evidence against unit root in nominal interest rate, which supports the ndings in Rose (1988) and raises doubt about economic results predicted by the CCAPM and optimal monetary policy models.…”
Section: Introductioncontrasting
confidence: 53%
“…For example, the 7 Three-month and twelve-month Treasury Bill Rate: Board of Governors of the Federal Reserve System, http://www.stls.frb.org/fred/ 8 The data were pre-whitened using the deterministic speci cation and number of lags shown in table 9. presence of unit root in RER implies that PPP hypothesis does not hold in the long run even if we account for heavy tails in real exchange rates. In a recent paper, Falk and Wang (2003) reached the same conclusion by considering the effects of fat tails on critical values of cointegrating tests. In particular, they nd that the Johansen´s likelihood-ratio based test are less supportive of PPP when Gaussianbased critical values are replaced by heavy-tailed-based critical values.…”
Section: Nominal Interest Rate and Real Exchange Ratementioning
confidence: 56%
See 1 more Smart Citation
“…The validity of the PPP hypothesis has generated a great deal of controversy, intimately related to the type of method applied. Recently, Falk and Wang (2003) found that PPP hypothesis holds against some economies but not for all. Their work is based on Caner's (1998) concept of cointegration where the VECM errors follow a stable distribution.…”
Section: An Empirical Applicationmentioning
confidence: 99%
“…We use the same data as Falk and Wang (2003), downloaded from the Journal of Applied Econometrics data archive website. The domestic country is the US and the bilateral relationship of study is with Canada, France, Germany, Italy, Japan, and the U.K..…”
Section: An Empirical Applicationmentioning
confidence: 99%